Contribution Of Farming Mushrooms (Volvariella Volvacea) To Farmer’s Household Income In Cilamaya Kulon District Karawang - Resty Nurfrida; Abubakar Abubakar; Luthfi Nur’azkiya (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2022)
Mushroom is one of the horticultural crops that have high business potential in Cilamaya Kulon District, Karawang Regency due to high market demand. The purpose of the research are to determine the income of mushroom farming, household income of farmers, the contribution of mushroom farming to household incomes of farmers, the level of main and secondary income of mushroom farmers. The research method used is descriptive quantitative method. This research uses primary data and secondary data. Primary data collection by interview technique using a questionnaire. The research was carried out from November to December 2021 by simple random sampling of 30 respondents of mushroom farmers in Cilamaya Kulon District, Karawang Regency. The analysis technique used are farm income analysis and descriptive percentage. The results showed that the average income of mushroom farming in one month was Rp2.180.770 and Rp4.959.063 for the average household income of farmers. The contribution of mushroom farming is 44,02% including the moderate level of contribution to the household income of farmers. The main and secondary income levels are 44,02% and 55,98% including the moderate level of contribution to the household income of farmers in Cilamaya Kulon District, Karawang Regency.